2005
DOI: 10.33151/ajp.3.3.321
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for Assessments of Mental Illness in Paramedic Practice: A New Theoretical Framework

Abstract: This is the third paper in a series that heralds a study that examines paramedic accounts and constructs of judgment and decision-making (JDM) of mental health and mental illness. This paper will overview an innovative theoretical framework for conducting a discourse-historical case study of paramedic judgment and decision-making of mental health and mental illness using ethnographic and ethnomethodological research methods. The review of the existing research and literature suggests an insufficiency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 11 publications
2
21
0
Order By: Relevance
“…Knowledge levels relating to both mental status assessments and agitated patients from both a clinical practice and theoretical perspective were noted to have improved at the completion of the advanced mental health subject. Literature suggests that there is a need for appropriate paramedic educational opportunities from which this knowledge can be gained (5,7).…”
Section: Discussion (Continued) General Knowledge About Mental Illnesmentioning
confidence: 99%
“…Knowledge levels relating to both mental status assessments and agitated patients from both a clinical practice and theoretical perspective were noted to have improved at the completion of the advanced mental health subject. Literature suggests that there is a need for appropriate paramedic educational opportunities from which this knowledge can be gained (5,7).…”
Section: Discussion (Continued) General Knowledge About Mental Illnesmentioning
confidence: 99%
“… 3 Researchers thus recommend restructuring emergency mental health care systems 3 and further addressing mental health calls in the training of paramedics, an approach that the profession supports. 21 - 23…”
Section: Paramedic Services In the Academic Literaturementioning
confidence: 99%
“…Yet another issue we would like to explore and problematize is the suggestion that increased mental health call volumes for paramedics should be addressed with further training 18 , 20 - 22 , 32 and more and better mental health services in the community. 3 , 14 , 16 , 19 Surely both suggestions are useful—all else equal.…”
Section: What Is Missing In Dominant Approaches?mentioning
confidence: 99%
“…Despite such rulings, these situations remain complex from the paramedic perspective. Paramedics in the present study report having limited support and referral pathways for SH, and lack of access to medical staff and AMHPs with legal (Shaban et al 2005), such legislation is reflective of the current UK context of police and paramedics managing SH patients in crisis with limited access to medical professionals. As paramedics are often the only registered health professional in attendance following SH, it may therefore be appropriate for legislation, mental health policy, education and practices to be amended to reflect the vital role of paramedics providing medical and mental health assessments to people who SH, along with their ability to refer to a range of services.…”
Section: Legislationmentioning
confidence: 90%
“…Applying legislation has been reported to negatively influence attitudes of nurses towards SH (McAllister et al 2002), who identified four dimensions explaining variations in attitudes towards people who SH which included perceived confidence in assessment and referral, ability to deal with clients, legal and hospital regulations guiding practice, and an empathic approach. Paramedics in Australia have also reported similar challenges with legislation within their wider care for people presenting with mental health problems (Shaban 2005).…”
Section: Legislationmentioning
confidence: 97%